2003
DOI: 10.1194/jlr.m300183-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

12-Hydroxyeicosatetraenoic acid participates in angiotensin II afferent arteriolar vasoconstriction by activating L-type calcium channels

Abstract: The arachidonate lipoxygenase (LO) product, 12(S)-hydroxyeicosatetraenoic acid (12(S)-HETE), has been implicated as a key contributor to the pathogenesis of atherosclerosis, hypertension, and diabetic nephropathy (1-4). 12-LO expression has been detected in renal vascular and glomerular cells, and these cells have the capacity to produce 12(S)-HETE (5-8). In addition to its involvement in glomerular inflammation and vascular smooth muscle cell growth, 12(S)-HETE is a renal vasoconstrictor (5,(8)(9)(10). 12(S)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 38 publications
4
40
0
Order By: Relevance
“…In agreement, other studies have shown that a lack of NO (which has vasorelaxant properties in the pulmonary arteries) may also contribute to endothelial dysfunction, especially in pulmonary hypertension-induced HAPE (Bailey et al, 2010). In addition, we found significant increase in ROS-dependent 15-HETE and 12-HETE, which both are known to have vasoconstrictive properties (Burhop et al, 1988;Nishiyama et al, 1998;Yiu et al, 2003). The essential amino acid tryptophan, the biogenic amines serotonin, and SDMA, which all are supposed to have vasoconstrictive function in pulmonary vessels, also increased significantly during the high altitude stay.…”
supporting
confidence: 92%
“…In agreement, other studies have shown that a lack of NO (which has vasorelaxant properties in the pulmonary arteries) may also contribute to endothelial dysfunction, especially in pulmonary hypertension-induced HAPE (Bailey et al, 2010). In addition, we found significant increase in ROS-dependent 15-HETE and 12-HETE, which both are known to have vasoconstrictive properties (Burhop et al, 1988;Nishiyama et al, 1998;Yiu et al, 2003). The essential amino acid tryptophan, the biogenic amines serotonin, and SDMA, which all are supposed to have vasoconstrictive function in pulmonary vessels, also increased significantly during the high altitude stay.…”
supporting
confidence: 92%
“…Leukotriene A 4 -derived eicosanoids (from the LO pathway) have been shown to act on the microcirculation by enhancing vasoconstriction and vascular permeability (via LTC 4 and LTD 4 ), and by mediating the local inflammatory response to increase polymorphonuclear leukocyte aggregation and adhesion to the endothelium (LTB 4 ) (92-94). Hydroxyeicosatetraenoic acids (HETEs) and epoxyeicosatrienoic acids (EETs) from the P450 monooxygenase pathway can constrict renal vessels and glomerular mesangial cells and have been implicated in the tubuloglomerular feedback and renal blood flow autoregulation of the kidney (95,96). Further details on the complex renal pathophysiology of eicosanoids can be found in a recent dedicated review (83).…”
Section: Microvascular Dysfunction and The Balance Between Vasoconstrmentioning
confidence: 99%
“…12-and 15-HETE constrict renal vessels and glomerular mesangial cells. 12-HETE induces VSM growth and partly mediates ANG II-induced afferent arteriolar vasoconstriction, as well as TGF-␤ and ANG II-induced mesangial cell hypertrophy and ECM accumulation (192). 12/15-Lipooxygenase inhibition or gene deletion blunts the pressor response to ANG II and blocks ANG II-induced hypertrophy and ECM accumulation in rat mesangial cells (85).…”
Section: Renal Endothelial Cell Dysfunction In Htnmentioning
confidence: 99%